Enhanced ion transport in Li2O and Li2S films. Issue 53 (8th June 2021) - Lorger, Simon; Narita, Kai; Usiskin, Robert; Maier, Joachim
Abstract : Li2 O and Li2 S films show Li + conductivities comparable to those of typical SEI passivation layers in batteries. Abstract : Films of Li2 O and Li2 S grown by sputter deposition exhibit Li + conductivity values at room temperature which are enhanced by 3–4 orders of magnitude relative to bulk samples. Possible mechanisms are discussed. The results may help explain the ion transport pathway through passivation layers containing these chalcogenides in batteries.